PENGARUH GREEN FINANCE DAN FINANCIAL LITERACY TERHADAP BUSINESS SUSTAINABILITY DENGAN FINANCIAL BEHAVIOR SEBAGAI VARIABEL MEDIASI - Fitriana; Leonardo Davidsi Sipayung; Aryan Agus Pratama (Media Mahardhika, 2026)
The effort to maintain business sustainability in the micro, small, and medium-sized enterprise (MSME) sector is increasingly associated with financial literacy and sustainability-oriented financing practices. In this context, this study investigates the roles of green finance and financial literacy in influencing business sustainability, with financial management behavior positioned as a mediating variable. The study adopts a quantitative approach involving 150 MSME owners as respondents. Data were collected through a structured questionnaire and subsequently analyzed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) technique to examine both direct and indirect relationships among the variables. The empirical findings indicate that the implementation of green finance and the level of financial literacy possessed by business owners significantly contribute to the enhancement of business sustainability. In addition, financial management behavior was found to have a direct effect on business sustainability. Furthermore, financial management behavior functions as a mediating variable that strengthens the relationships between green finance and financial literacy and business sustainability. These findings underscore that the combination of adequate financial knowledge and access to sustainable financing schemes can foster more adaptive and effective financial management behavior. Ultimately, this becomes an important factor in supporting the resilience and long-term sustainability of MSMEs. Therefore, strengthening financial literacy and expanding access to sustainable financing instruments should become priorities in the formulation of MSME empowerment policies.